Damage mechanism and mode of square reinforced concrete slab subjected to blast loading - Zhao, C.F.; Chen, J.Y. (Theoretical and applied fracture mechanics, 2013)
Reinforcement concrete is the principle material for military engineering and nuclear power plant. However, impact and explosions could completely destroy such structures, causing tremendous casualties and property loss. Therefore, analyzing the damage mechanism and mode of the structures under blast loading is significant. The objective of this paper is to investigate the dynamics response and damage mechanism of three 1000mm×1000mm×400mm reinforcement concrete slabs subjected to 400mm standoff distance close-in explosions using LS-DYNA software and compare with experimental tests. A three-dimensional material model including explosive, air and reinforcement concrete slab with separated modeling method taking into account Arbitrary Lagrange–Euler, multiple materials algorithms and fluid–structure coupling interaction, is created to simulate the experiments. The sophisticated concrete and reinforcement bar material models, considering the strain rate effects, dynamic increasing factor and equation of state for concrete, are applied in simulating the damage mechanism and dynamic response. From the numerical results and comparison of the experimental data, it can be seen that the numerical results and experimental data shows a favorable agreement and the present model can still give a reliable prediction of the damage characteristic for the reinforcement concrete slabs. It also observed that the increase of the amount of the explosive can change the failure mode of the slab.